Do nutrition-sensitive agriculture interventions work among ethnic minorities in Northern Vietnam amidst the COVID-19 crisis? - Nguyen, Lan Thuy T.; Van den Berg, Marrit; Stomph, TjeerdJan; Nabuuma, Deborah (Springer, 2025)
Undernutrition remains a significant challenge among ethnic minorities in Northern Vietnam, possibly due to limited diet diversity. Our study explored the potential of a nutrition-sensitive agriculture intervention (NSA) to improve diet quality among the Thai, H’Mong, and Dao communities using a mixed-methods approach. Conducted between December 2020 and July 2022 during the COVID-19 pandemic, the study involved 600 households across 36 clusters, divided into two treatment groups: one received nutrition and agricultural training, another received this training plus a variety of vegetable seeds, and a control group without any intervention. We focused on diet and crop diversity, especially in vegetables and legumes. Quantitative data were collected through one baseline and two end-line rounds to ensure sufficient statistical power, while qualitative data included 14 focused group discussions, seven in-depth interviews, and field notes from field assistants. Our findings revealed that diet diversity, particularly in vegetables and legumes, was limited among the H’Mong and Dao, underscoring the potential of NSAs to improve their diet. Market access and on-farm production were found to complement each other in enhancing both diet and crop diversity across all three communities. The impact of the NSA intervention highlighted the complexity of contextual factors, including initial conditions and the ongoing effects of the COVID-19 pandemic, which influenced the outcomes in unpredictable ways. Nonetheless, combining seed provision with nutrition and agricultural training emerged as a promising strategy to enhance both diet and crop diversity, particularly given the strong vegetable cultivation practices and limited market access in these communities.